Superimposition of 3D maxillary digital models using open-source software - Anacleto,Murilo Augusto (2019)
Abstract Historically, whether for research purposes or clinical monitoring, orthodontic evaluation of dental movements has been done using plaster study models and two dimensional (2D) radiographs. However, new frontiers for the diagnosis, planning and outcome assessment of orthodontic treatments have arisen, due to the revolutionary digital tools which enable a three dimensional (3D) computerized analysis of dental movements by means of digital models. However, the software for 3D analysis are often costly, resulting in limited access to orthodontists. The present study aims to describe, through a clinical case presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics, a method for the superimposition of maxillary digital models using an open-source software to evaluate dental movements.